Anxiety and depression in older patients: the role of culture and acculturation - Anna Zisberg (BMC, 2017)
Abstract Background Anxiety and depression are major health concerns in general among older adults and especially during hospitalization, as they lead to numerous negative outcomes. There is currently no sufficient body of research examining the role of cultural background in patients' experience of these conditions. Better identifying patients at risk may help reduce inequity and provide patient-centered, culturally sensitive care. The current study explores the roles of culture and acculturation in anxiety and depression levels in recent and veteran Russian immigrants compared with native Israelis and veteran immigrants from Middle Eastern countries. Methods Secondary analysis of a prospective cohort study of cognitively intact older adults (70+) hospitalized for acute conditions in internal medical units in two hospitals in Israel during 2009-11. Depression and anxiety were assessed within 48 h of admission through personal interview using the Tucker Depression Rating and the Short Anxiety Screening Tests. Demographic and health data were collected from electronic health records. Immigration status was defined by country and emigration year. Study hypotheses were tested employing analyses of covariance, modeling anxiety and depression symptoms separately, controlling for potential confounders. Results Significant differences between study groups were observed in fully adjusted models for anxiety symptoms (F [3, 515] = 5.24, p < .01) when both veteran (21 ± 5.83) and recent (20.2 ± 5.23) Russian immigrants expressed higher anxiety levels than native Israelis (18.35 ± 5.23) and veteran immigrants (18 ± 5.03) (from p = .05 to p < 0.01). No significant differences were found in anxiety symptoms between recent and veteran Russian immigrants. Both depression and anxiety symptoms showed an interaction effect of study immigration groups by sex: while no differences were observed among native Israelis, significantly higher depression and anxiety were observed among women than men in the other groups. Conclusions Culture of origin may play a central role in determining expression of anxiety symptoms and perhaps modify acculturation. During hospitalization, special attention should be given to the level of anxiety among not only recent but also veteran immigrants. Further research may explore whether elevated anxiety is a result of stress due to hospitalization or a stable trait.